Implementing Standardized Work : Measuring Operators' Performance. - Patchong, Alain (CRC Press, 2012)
Introduction A Strange Day in a New Plant: The ""Beheaded Chicken"" Variability Is the Enemy of Production Training Day One: Introducing Standardized Work The Hidden Cost of Human Variability How to Measure Operator Performance The Variability Index A-Rank, B-Rank, C-Rank and D-Rank Operators Initial Operator Performance Mapping (OPM) Detailed Standardized Work Deployment Steps Epilogue: The Quest for Mode 80.